2020
DOI: 10.31234/osf.io/5djkh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confidence Intervals on Implicit Association Test Scores Are Really Rather Large

Abstract: Implicit association test scores are presented as point estimates. Unusually for a psychological measure, individual scores are not tested for statistical significance in standard practice. This study estimates individual confidence intervals for a large dataset of IAT scores. The intervals are large. Only half of scores are significantly different from zero. This result raises theoretical concerns about standard interpretations of the IAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
13
1
Order By: Relevance
“…By contrast, generative modeling facilitates development of theory-informed models of behavior and takes advantage of all the information available, thereby improving accuracy of inference even when using smaller samples of behavioral (or neural) data. Our results question conclusions drawn from previous studies on reliability of various behavioral and neural measuresparticularly those that relied on two-stage approaches (e.g., Chen et al, 2015;Elliott et al, 2020;Enkavi et al, 2019;Gawronski et al, 2017;Hedge et al, 2017;Klein, 2020;Noble et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By contrast, generative modeling facilitates development of theory-informed models of behavior and takes advantage of all the information available, thereby improving accuracy of inference even when using smaller samples of behavioral (or neural) data. Our results question conclusions drawn from previous studies on reliability of various behavioral and neural measuresparticularly those that relied on two-stage approaches (e.g., Chen et al, 2015;Elliott et al, 2020;Enkavi et al, 2019;Gawronski et al, 2017;Hedge et al, 2017;Klein, 2020;Noble et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Such findings have since been replicated and extended to wide range of self-control tasks (Enkavi et al, 2019). Other behavioral tasks that are used widely throughout the behavioral sciences, including the IAT, also show similarly low test-retest correlations (r = .01-.72; average of r ≈ .4) across versions and timepoints (Gawronski et al, 2016;Klein, 2020). In the brain sciences, similarly low intraclass correlation coefficients were found in a meta-analysis of 90 experiments (mean ICC=0.397), and poor reliability of activity in regions of interest of brain regions across 11 common tasks used within the Human Connectome Project and the Dunedin Study (ICCs=0.067-0.485; Elliott et al, 2020).…”
Section: The Reliability Paradoxmentioning
confidence: 82%
“…It is also worth noting that similar analyses of data from another implicit measure, the Implicit Association Test, suggests that the IRAP's estimation precision is substantially worse than the IAT's (IRAP MAP 95% CI width = 1.33, IAT MAP 95% CI width = 0.75: see Hussey, 2020;Klein, 2020).…”
Section: Confidence Interval Widthmentioning
confidence: 99%
“…Implicit measures have become enveloped in this measurement crisis. Recent research has shown that the IAT does not conform to the measurement model which has formerly been specified for it; whereas it has previously been argued that the IAT captures a distinct latent variable to explicit measures Dovidio et al, 2001), research increasingly suggests that the IAT and explicit measures likely capture the same construct and differ primarily in their measurement precision (Schimmack, 2019a;Connor & Evers, 2020;Klein, 2020;Dalege & van der Maas, 2020). Likewise, recent evidence also suggests that the AMP only conforms to its assumed measurement model when awareness of the influence of primes in the task is high (i.e., the measure is either implicit or valid for participants, but not both simultaneously; .…”
Section: Specify and Test Psychometric Propertiesmentioning
confidence: 99%
“…At times, the poor test-retest reliability of implicit measures relative to explicit measures is often dismissed under the premise that the construct captured by implicit measures is nosier than that captured by explicit measures Brownstein et al, 2020;Dalege & van der Maas, 2020). Yet given the recent evidence that implicit measures likely capture the same construct as explicit measures (Schimmack, 2019a), combined with the poor estimation of individual implicit measure scores (Klein, 2020;Hussey, 2020), it seems much more likely that the measurement procedures themselves are simply nosier than their explicit equivalents. This, then, represents a fundamental barrier to the validity of these measures.…”
Section: Specify and Test Psychometric Propertiesmentioning
confidence: 99%